1992
DOI: 10.21273/jashs.117.6.925
|View full text |Cite
|
Sign up to set email alerts
|

Respiration Rate of Blueberry in Modified Atmosphere at Various Temperatures

Abstract: Respiration rates of three blueberry (Vaccinium corymbosum L.) cultivars (Coville, Blueray, and Jersey) were measured as a function of O2, CO2, and temperature using the closed system method. The data conformed well to a recently proposed Michaelis-Menten type respiration (r) model (r = Vm [O2]/{Km + (1 + [CO2]/Ki)[O2]}), where V Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 7 publications
(10 reference statements)
4
41
0
2
Order By: Relevance
“…Although, an exact transition temperature is difficult to establish from Fig. 6, it appears to be in agreement with the observation of Song et al (1992) that the transition takes place in the vicinity of 15°C…”
Section: Modelsupporting
confidence: 87%
See 1 more Smart Citation
“…Although, an exact transition temperature is difficult to establish from Fig. 6, it appears to be in agreement with the observation of Song et al (1992) that the transition takes place in the vicinity of 15°C…”
Section: Modelsupporting
confidence: 87%
“…A close observation of the plot showed that the plot actually appeared to have two regions. Similar results were also observed by Song et al (1992) and Jaime et al (2001). This was attributed to a change in the rate limiting enzymatic action, as each enzyme may be affected differently by changes in temperature.…”
Section: Modelsupporting
confidence: 81%
“…Non-competitive models published for intact 'Conference' pear (de Wild et al, 1999;Lammertyn et al, 2001Lammertyn et al, , 2003Ho et al, 2006Ho et al, , 2008 did not make K m;O 2 and K mn;CO 2 temperature-dependent. A constant K m;O 2 was obtained for ten fresh-cut vegetables (Jacxsens et al, 2000) and packaged raspberry fruit for the temperature range from 0 to 20°C (Joles et al, 1994), while for blueberry a temperature effect on K m;O 2 was found (Song et al, 1992;Cameron et al, 1994). Ho et al (2006) indicated for cortex tissue of 'Conference' pear a K m;O 2 of 1.16 kPa, similar to K m;O 2 found for fresh-cut 'Rocha' pear (Table 4).…”
Section: Modelling the Effect Of Oxygen And Temperature On Respiratiosupporting
confidence: 58%
“…Fruit respiration rate was monitored at weekly intervals by a static method. The berries were allowed to respire for about 6 h inside air-tight glass bottles having a silicone septum on the lid (Song et al, 1992;Ratti et al, 1996). The head space gas composition inside the bottles was analyzed using a Gas chromatograph (SRI Instruments Inc., California, USA; Model-8610A) equipped with a thermal conductivity detector.…”
Section: Hvef Treatment Proceduresmentioning
confidence: 99%